Reducing the incidence of pregnancy-related urinary tract infection by improving the knowledge and preventive practices of pregnant women. (October 2019) - Navarro, Annalyn; Sison, Joanna Marie; Puno, Royces; Quizon, Teddy; Manio, Lee Jasper John; Gopez, Jeanelle; Tiongco, Raphael Enrique; Bundalian, Reynaldo
Abstract: Objective: Pregnancy-related urinary tract infections (UTI) is the leading cause of obstetrical ward admissions and is responsible for poor maternal and perinatal outcomes. This study aimed to reduce the incidence of UTI by improving the knowledge and preventive practices of pregnant women through the implementation of a health education package. Study Design: A health education package consisting of a seminar, sending of weekly text messages, and distribution of educational leaflets on UTI awareness and prevention was implemented in various rural health units in Pampanga, Philippines. A structured questionnaire was used to assess the pre- and post-intervention knowledge and preventive practices of pregnant women. Whereas, urinalysis results from the various rural health units were used to assess the incidence of UTI among the respondents. Results: Significant improvement ( p < 0.001) was observed regarding the participant's knowledge and water intake after the intervention. Although there was no significant change ( p = 0.16) in their hygiene statistically, all participants had improvements in hygiene practices after the intervention. The number of pregnant women who were positive for UTI also decreased significantly ( p < 0.001) following the intervention. Conclusion: The implemented health education package was able to reduce the incidence of pregnancy-related UTI by improving the knowledge and preventive practices of pregnant women.